Revision of Emphytopsis Wei & Nie (Hymenoptera: Tenthredinidae) with descriptions of seven new species from China and Japan - Wei, Meicai; Xu, Yi; Niu, Gengyun (Zootaxa, 2011)
Emphytopsis Wei & Nie, 1998 of Allantinae, Tenthredinidae is revised. Seven species are described as new: Emphytopsis nigricornis Wei & Xu, sp. nov., E. quadrata Wei & Xu, sp. nov., E. unimaculata Wei, sp. nov., E. zhongi Wei & Niu, sp. nov., E. lii Wei, sp. nov. from China, E. shinoharai Wei & Niu, sp. nov. and E. flatoserrula Wei, sp. nov. from Japan. E. nigromaculata (Takeuchi, 1952) new combination is transferred from Taxonus Hartig. A key to the species of the genus is presented. Emphytopsis punctata Wei & Nie, 1998 and E. nigromaculata (Takeuchi) are redescribed. The previously unknown male of E. punctata is described.